Longitudinal Links between Adolescent and Peer Conduct Problems and Moderation by a Sensitivity Genetic Index. (31st October 2020) - Schlomer, Gabriel L.; Cleveland, H. Harrington; Feinberg, Mark E.; Murray, Jessica L.; Vandenbergh, David J.
Abstract : The most extensively studied influence on adolescent conduct problem behaviors is peers, and the literature points to genetics as one source of individual differences in peer influence. The purpose of this study was to test the hypothesis that an environmental sensitivity genetic index comprised of DRD4, 5‐HTTLPR, and GABRA2 variation would moderate the association between peer and adolescent conduct problems. Latent growth modeling was applied to PROSPER project longitudinal data from adolescents and their peers. Results showed the hypothesis was supported; adolescents with more copies of putative sensitivity alleles were more strongly influenced by their peers. The interaction form was consistent with differential susceptibility in follow‐up analyses. Strengths and weaknesses of genetic aggregates for sensitivity research are discussed.